2023
DOI: 10.1098/rspb.2022.2129
|View full text |Cite
|
Sign up to set email alerts
|

A 17-year time-series of fungal environmental DNA from a coastal marine ecosystem reveals long-term seasonal-scale and inter-annual diversity patterns

Abstract: Changing patterns in diversity are a feature of many habitats, with seasonality a major driver of ecosystem structure and function. In coastal marine plankton-based ecosystems, seasonality has been established through long-term time-series of bacterioplankton and protists. Alongside these groups, fungi also inhabit coastal marine ecosystems. If and how marine fungi show long-term intra- and inter-annual diversity patterns is unknown, preventing a comprehensive understanding of marine fungal ecology. Here, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Coastal planktonic fungi typically constitute a mixture of marine and terrestrial lineages (Chrismas et al., 2023). There are currently 1,898 described species of marine fungi (https://www.marinefungi.org/, 12 September 2023; Calabon et al., 2023), but their actual diversity is estimated to be much higher, with some studies stating that only around 1% of marine fungi have been identified (Gladfelter et al., 2019; Jones, 2011).…”
Section: Diversity Of Planktonic Marine Fungimentioning
confidence: 99%
“…Coastal planktonic fungi typically constitute a mixture of marine and terrestrial lineages (Chrismas et al., 2023). There are currently 1,898 described species of marine fungi (https://www.marinefungi.org/, 12 September 2023; Calabon et al., 2023), but their actual diversity is estimated to be much higher, with some studies stating that only around 1% of marine fungi have been identified (Gladfelter et al., 2019; Jones, 2011).…”
Section: Diversity Of Planktonic Marine Fungimentioning
confidence: 99%
“…In addition to saprotrophy, marine yeasts are associated with other trophic interactions, including predation by zooplankton (Cleary et al 2016 ), and parasitism of phytoplankton (Li et al 2016 ) and zooplankton (Seki and Fulton 1969 ). Marine yeast abundances have been shown to fluctuate by several orders of magnitude over relatively short time-scales during a spring phytoplankton bloom (Priest et al 2021 ), while interannual recurrence patterns of yeast-containing taxa further suggest a dynamic role for yeasts in marine plankton communities (Taylor and Cunliffe 2016 , Chrismas et al 2023 ). Absolute abundances of marine yeast taxa have been significantly positively correlated with environmental concentrations of nitrogen-containing compounds (Taylor and Cunliffe 2016 , Priest et al 2021 ), but quantitative data describing marine yeast responses to nitrogen availability are currently lacking in contrast with other major plankton groups.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main limiting factors for DNA-based assessment of mycoplankton is the bias from "generic" eukaryotic primers (targeting the 18S rRNA gene [ 13 ]), which can lead to a lack of amplified fragments and consequently an underestimation of the proportion and diversity of fungi in biological communities [ 9 , 14 ]. Therefore, the use of fungal-specific barcodes, such as those targeting the ribosomal nuclear gene internal transcribed spacer (ITS) [ 15 ] or the 18S rRNA gene [ 16 ], can provide greater insight into marine fungi biodiversity, although requiring ad hoc amplification, sequencing, and data analysis. In addition, mycoplankton can have patchy and highly variable spatiotemporal distribution patterns compared to bacterioplankton [ 9 , 15 , 17 ], making data analysis and interpretation more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of fungal-specific barcodes, such as those targeting the ribosomal nuclear gene internal transcribed spacer (ITS) [ 15 ] or the 18S rRNA gene [ 16 ], can provide greater insight into marine fungi biodiversity, although requiring ad hoc amplification, sequencing, and data analysis. In addition, mycoplankton can have patchy and highly variable spatiotemporal distribution patterns compared to bacterioplankton [ 9 , 15 , 17 ], making data analysis and interpretation more complex. Therefore, additional efforts are needed to explore the diversity and ecological role of fungi in marine habitats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation